Antenatal care and skilled delivery service utilisation in Somali pastoral communities of Eastern Ethiopia. Issue 3 (9th December 2019) - Umer, A.; Zinsstag, J.; Schelling, E.; Tschopp, R.; Hattendof, J.; Osman, K.; Yuya, M.; Ame, A.; Zemp, E.
Abstract: Objective: To assess maternal health care service utilisation and associated factors in Somali pastoral communities of eastern Ethiopia. Methods: Community‐based cross‐sectional study complemented by qualitative assessments in Adadle district, Somali region, eastern Ethiopia, among 450 women in six kebeles from August to September 2016. Logistic regression was used to assess factors associated with antenatal care use and skilled delivery care use, controlling for confounders. Results: About 27% [95%CI 22.8–31.2%] of women used antenatal care, and 22.6% [95%CI 18.7–26.5%] received skilled delivery service. None of the respondents reported post‐natal care. About 43% reported that they had no knowledge of antenatal care, and 46% did not perceive delivery at a health facility as important. Pastoral lifestyle, husband's educational status, women's attitude towards health care service and financial support from the husband were significantly associated with antenatal care utilisation. Health professionals' attitudes, perceptions of institutional delivery, antenatal care utilisation and information about exemptions from maternal health care fees were associated with skilled delivery service utilisation. Conclusion: Improving community awareness of antenatal care, employing female health professionals and culturally adapted guidelines could improve skilled delivery utilisation. In a patriarchal society, involving male partners in all maternal health issues is essential to increase use of maternal health services and to decrease maternal mortality. Abstract : Objectif: Evaluer l'utilisation des services de soins de santé maternelle et les facteurs associés dans les communautés pastorales somaliennes dans l'est de l'Ethiopie. Méthodes: Etude transversale basée sur la communauté complétée par des évaluations qualitatives dans le district d'Adadle, région somalienne, dans l'est de l'Ethiopie, portant sur 450 femmes dans six kebeles d'août à septembre 2016. Une régression logistique a été utilisée pour évaluer les facteurs associés à l'utilisation des soins prénatals et à l'accouchement sous soins qualifiés, en ajustant pour les facteurs confusionnels. Résultats: 27% [IC95%: 22.8–31.2%] des femmes ont utilisé des soins prénatals et 22, 6% [IC95%: 18.7‐26.5%] ont reçu des services d'accouchement qualifiés. Aucune des répondantes n'a signalé des soins postnatals. 43% ont déclaré qu'elles n'avaient aucune connaissance des soins prénatals et 46% ne percevaient pas l'accouchement dans un établissement de santé comme important. Le mode de vie pastoral, le niveau d'éducation du mari, l'attitude des femmes à l'égard des services de santé et le soutien financier du mari étaient significativement associés à l'utilisation des soins prénatals. Les attitudes des professionnels de la santé, les perceptions de l'accouchement en établissement, l'utilisation des soins prénatals et les informations sur les exemptions des frais de soins de santé maternelle ont été associées à l'utilisation des services d'accouchement qualifiés. Conclusion: Améliorer la sensibilisation de la communauté aux soins prénatals, employer des professionnels de la santé féminins et des directives culturellement adaptées pourrait améliorer l'utilisation de l'accouchement qualifié. Dans une société patriarcale, la participation des partenaires masculins à toutes les questions de santé maternelle est essentielle pour accroître l'utilisation des services de santé maternelle et réduire la mortalité maternelle.